2019
DOI: 10.1371/journal.pone.0221494
|View full text |Cite
|
Sign up to set email alerts
|

Cadaveric biomechanical testing of torque - to - failure magnitude of Bilateral Apical Vertebral Derotation maneuver in the thoracic spine

Abstract: It remains unclear what is the real safe limit of torque magnitude during Bilateral Apical Vertebral Derotation (BAVD) in thoracic curve correction. Up to author’s knowledge there is no study except this one, to reproduce in–vivo real measurements and intraoperative conditions during BAVD maneuver. The objective of this study was to evaluate the torsional strength of the instrumented thoracic spine under axial rotation moment as well as to define safety limits under BAVD corrective maneuver in scoliosis surger… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…Lou et al 40 measured correction forces between 22 and 57 N in seven patients in which AIS was corrected by means of the derotation manoeuvre and posterior fixation, which are in general lower than our average predicted value of 74 N. However, the literature study mostly focused on the description and validation of the measurement device, whereas the clinical data collection was relatively small and documented in a limited manner. Pankowski et al experimentally measured the torque-to-failure and angle-to-failure during the derotation manoeuvre in whole cadavers, finding average values of 73 Nm and 45° and failures most commonly located in the apical area 41 . Cheng et al compared failure loads after derotation with different instrumentation configurations, and concluded that linked constructs provided higher failure loads than single pedicle screws 42 .…”
Section: Discussionmentioning
confidence: 99%
“…Lou et al 40 measured correction forces between 22 and 57 N in seven patients in which AIS was corrected by means of the derotation manoeuvre and posterior fixation, which are in general lower than our average predicted value of 74 N. However, the literature study mostly focused on the description and validation of the measurement device, whereas the clinical data collection was relatively small and documented in a limited manner. Pankowski et al experimentally measured the torque-to-failure and angle-to-failure during the derotation manoeuvre in whole cadavers, finding average values of 73 Nm and 45° and failures most commonly located in the apical area 41 . Cheng et al compared failure loads after derotation with different instrumentation configurations, and concluded that linked constructs provided higher failure loads than single pedicle screws 42 .…”
Section: Discussionmentioning
confidence: 99%